Embryonic, Fetal, and Neonatal Complications in Infants of Diabetic Mothers: Insights from the Cincinnati Diabetes in Pregnancy Program Project Grant - Mimouni, Francis B.; Khoury, Jane C.; Ehrlich, Shelley; Rosenn, Barak M.; Sheffer-Mimouni, Galit; Miodovnik, Menachem (American Journal of Perinatology, 2024)
This study aimed to review how the Cincinnati Diabetes in Pregnancy Program Project Grant (PPG) contributed to the understanding and treatment of neonatal complications in infants of diabetic mothers (IDMs). This is a retrospective review of all PPG work on glycemic control at different pregnancy time points and its association with embryonic, fetal, and neonatal complications, such as congenital malformations (CMs), intrauterine growth restriction, macrosomia, hypoglycemia, respiratory distress syndrome (RDS), asphyxia, and polycythemia. We found that maternal vasculopathy and poor glycemic control during embryogenesis, but not frequency of maternal hypoglycemic episodes or insulin therapy, are independent risk factors for major CMs. A suggestive association of major CMs with maternal Magnesium deficiency was also observed. Poor glycemic control during late embryogenesis and early fetal development was associated with an increased risk of minor CMs. We described a biphasic pattern of fetal growth whereby early growth delay was followed by enhanced fetal growth associated with neonatal macrosomia. Macrosomia was associated with poorer glycemic control in the third trimester and an increased risk of birth trauma. Macrosomia was also correlated with animal-origin insulin concentrations in cord blood, demonstrating that insulin bound to antibodies can cross the placenta and may affect the fetus. We also showed that neonatal hypoglycemia was significantly associated with third-trimester glycemic control, in addition to hyperglycemia occurring during labor. With modern management and adequate prenatal care, IDMs are no longer at increased risk for RDS. Perinatal asphyxia was associated with increased proteinuria appearing in pregnancy, maternal hyperglycemia before delivery, and prematurity. Polycythemia in IDMs is prevalent and correlates with proxy measurements of fetal hypoxemia (nucleated red blood cells at delivery) and poorer glycemic control in late pregnancy. The PPG in its various phases revealed the important role of glycemic control at nearly every stage of pregnancy including labor.Key Points
Keywords: congenital malformation; respiratory distress syndrome; hypoglycemia; polycythemia; fetal hypoxemia